Writing about war: making sense of the absurd in Mileta Prodanović's novel Pleši, čudovište, na moju nežnu muziku (Dance, you monster, to my soft music) - Norris, David A. (Modern Humanities Research Association, 2013)
In the narrative of a mass conflict, the human experience of its effects may be subsumed into the rationalizing contours of history, or they may fall completely outside our comprehension. This article examines the intertextual strategies employed in Prodanović's novel about the war in former Yugoslavia. The text conveys the reality of the conflict by relating it through events and characters located in prior media constructions. The historical, documentary, mythic, and fictional sources focus on the signifying systems which drag the war into the horizon of expectations of those who were not there, closing the gap between reality and representation, life and art.